1995
DOI: 10.1128/jvi.69.11.7196-7204.1995
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of human immunodeficiency virus type 1 Vif requires membrane targeting by C-terminal basic domains

Abstract: Human immunodeficiency virus type 1 (HIV-1) encodes a Vif protein which is important for virus replication and infectivity. Vif is a cytoplasmic protein which exists in both membrane-associated and soluble forms. The membrane-associated form is an extrinsic membrane protein which is tightly associated with the cytoplasmic side of membranes. We have analyzed the mechanism of membrane targeting of Vif and its role in HIV-1 replication. Mutagenesis studies demonstrate that C-terminal basic domains are required fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 44 publications
3
42
0
Order By: Relevance
“…4 and 5). It has also been reported that the combined action of a number of positively charged amino acids toward Vif's carboxy terminus contributes to function (2,11,13). Although the substitution of the lysines at positions 157 and 160 had no effect on activity (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…4 and 5). It has also been reported that the combined action of a number of positively charged amino acids toward Vif's carboxy terminus contributes to function (2,11,13). Although the substitution of the lysines at positions 157 and 160 had no effect on activity (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Between these regions, conserved motifs were observed, in particular the SLQXLA motif located between amino acids 144 and 149 (Oberste and Gonda, 1992) and two other motifs in the last 30 C-terminal amino acids of the Vif protein, i.e., 161 PPLPS 165 and 168 KLTEDRWN 175 . These two latter motifs are located in the domain which is in association with the plasma membrane and with the Gagprecursor (Bouyac et al, 1997;Goncalves et al, 1995). Moreover Arg and Lys residues within the C-terminal end of Vif (8 to 11 residues between the positions 157 and 192), which are the most important residues for those interactions, are largely conserved in all LTNP as well as in late progressor Vif sequences.…”
Section: Definition Of the Asymptomatic Subjectsmentioning
confidence: 99%
“…Nevertheless, it was suggested that Vif is required at the time of particle production in the host cell for regulating virus assembly or maturation (2,3,11,35,49). Vif has been shown to associate with the cytoplasmic face of cellular membranes (17), a phenomenon that involves basic residues located in the C-terminal portion of Vif (18). Vif muta-tions that disrupt membrane association also affect Vif function (18), suggesting a correlation between membrane binding and Vif activity.…”
Section: The Human Immunodeficiency Virus Type 1 (Hiv-1) Vif Protein mentioning
confidence: 99%
“…Vif has been shown to associate with the cytoplasmic face of cellular membranes (17), a phenomenon that involves basic residues located in the C-terminal portion of Vif (18). Vif muta-tions that disrupt membrane association also affect Vif function (18), suggesting a correlation between membrane binding and Vif activity.…”
Section: The Human Immunodeficiency Virus Type 1 (Hiv-1) Vif Protein mentioning
confidence: 99%
See 1 more Smart Citation